Dietary nucleotide improves markers of immune response to strenuous exercise under a cold environment - Riera, J.; Pons, V.; Martinez-Puig, D.; Chetrit, C.; Tur, J. A.; Pons, A.; Drobnic, F. (Journal of the International Society of Sports Nutrition, 2013)
Strenuous exercise has been classically associated to immune-suppression and consequently to an increased risk of infections, especially at the upper respiratory tract. The administration of dietary nucleotides has been demonstrated useful to maintain the immune function in situations of stress and thus could be an appropriate strategy to counteract the decline of the immune function associated to strenuous exercise. The aim of the present study was to asses the impact of a specific nucleotide formulation (Inmunactive®) on the markers of immune function of athletes after a heavy exercise bout under cold conditions. Methods Twenty elite male taekwondo athletes were randomly divided into two groups of 10 subjects that were supplemented with placebo (P) or Inmunactive (I) at 480 mg/day during 30 days. At baseline (day 0) and after 4 wk of supplementation (day 30) each subject undertook an exhaustion exercise test using a cycloergometer. Skin temperature, core temperature, heart rate, lactate concentration and rating of perceived exertion (RPE) were recorded during the test. Blood and saliva samples were obtained before and after each exercise test for determination of blood cell concentrations, PHA-stimulated lymphocyte proliferation (PHA-LP) and salivary immunoglobulin A (SIgA). Results Exercise tests induced neutrophilia and reduction in lymphocyte blood counts on day 0 and on day 30 in both groups. However, the I group exhibited a faster recovery from the lymphopenic response than the P group, so that lymphocyte levels were higher after 150 min (P < 0.0028). Furthermore, the lymphoproliferative response was modulated by nucleotide supplementation, since it was higher in the I group on day 30 despite an almost significant (P < 0.06) exercise-evoked decrease at baseline. Conclusions These findings suggest that supplementation with a nucleotide-based product for 4 weeks could counteract the impairment of immune function after heavy exercise.